Study of ITO@PMMA composites by transmission electron microscopy - Arlindo, Elen P. S. [UNESP]; Orlandi, Marcelo Ornaghi [UNESP] (Springer Nature, 2011)
ITO nanowires were synthesized by carbothermal reduction process, using a co-evaporation method, and have controlled size, shape, and chemical composition. The electrical measurements of nanowires showed they have a resistance of about 102 Ω. In order to produce nanocomposites films, nanowires were dispersed in toluene using an ultrasonic cleaner, so the PMMA polymer was added, and the system was kept under agitation up to obtain a clear suspension. The PMMA polymer was filled with 1, 2, 5 and 10% in weight of nanowires, and the films were done by tape casting. The results showed that the electrical resistance of nanocomposites changed by over 7 orders of magnitude by increasing the amount of filler, and using 5 wt% of filler the composite resistance decreased from 1010 Ω to about 104 Ω, which means that percolation threshold of wires occurred at this concentration. This is an interesting result once for nanocomposites filled with ITO nanoparticles is necessary about 18% in weight to obtain percolation. The addition of filler up to 10 wt% decreased the resistance of the composite to 103 Ω, which is a value close to the resistance of wires. The composites were also analyzed by transmission electron microscopy (TEM), and the TEM results are in agreement with the electrical ones about percolation of nanowires. These results are promising once indicates that is possible to produce conductive and transparent in the visible range films by the addition of ITO nanowires in a polymeric matrix using a simple route. © 2011 Materials Research Society.
Keywords: Chemical compositions; Co-evaporation method; Controlled size; Electrical measurement; Electrical resistances; ITO nanowires; Orders of magnitude; Percolation thresholds; Polymeric matrices; Tape casting; Ultrasonic cleaners; Visible range; Carbothermal reduction; Conductive films; Fillers; Nanocomposite films; Nanocomposites; Nanowires; Polymer films; Polymeric films; Solvents; Toluene; Transmission electron microscopy; Ultrasonic cleaning; Wire; Filled polymers